2009
DOI: 10.3109/10428190903440953
|View full text |Cite
|
Sign up to set email alerts
|

SUVmax in FDG-PET at the biopsy site correlates with the proliferation potential of tumor cells in non-Hodgkin lymphoma

Abstract: The maximum standard uptake value (SUVmax) of the whole body on 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) reflects the tumor aggressiveness in non-Hodgkin lymphoma (NHL). To clarify the correlation between SUVmax at the biopsy site and the proliferation potential of tumor cells, we studied 36 patients with untreated NHL and five with untreated Hodgkin lymphoma (HL) by measuring the Ki-67 proliferation index (MIB-1 labeling index) in biopsy specimens. The measured MIB-1 labeling index was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 11 publications
4
35
0
Order By: Relevance
“…Previous studies suggested the association between SUV max and tumor aggressiveness [21][22][23]. And recently, the fact that proliferation potential of tumor cells measured by Ki-67 stain positively correlated with SUV max has been reported [24][25][26][27][28]. However, the measurement of SUV max has confined to the detection of the most obvious metabolic activity of the tumor at single site, but not the overall tumor activity.…”
mentioning
confidence: 99%
“…Previous studies suggested the association between SUV max and tumor aggressiveness [21][22][23]. And recently, the fact that proliferation potential of tumor cells measured by Ki-67 stain positively correlated with SUV max has been reported [24][25][26][27][28]. However, the measurement of SUV max has confined to the detection of the most obvious metabolic activity of the tumor at single site, but not the overall tumor activity.…”
mentioning
confidence: 99%
“…This is of interest, because only the image pattern, but not the underlying information (i.e., tumor property) assessed is similar between the two techniques: DWI visualizes intercellular space narrowing, and thus, cell density (35); whereas 18F-FDG-PET visualizes glucose metabolism, which in turn has been shown to correlate with cell proliferation (36,37). We hypothesize that the reason for our findings is that, at least in the FDG-avid lymphomas included in the present study, there is more glucose consumption in areas of higher cell density, such a correlation between cell density and glucose metabolism has already been reported for malignant lung nodules and pancreatic adenocarcinoma (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding systemic NHL, Watanabe et al recently reported a strong correlation between the Ki-67 proliferating index and the SUV max of the biopsy site and proposed SUV max as a useful predictor for the proliferation potential of NHL (37). Transferring these findings to primary CNS lymphoma would be difficult since these cells usually have an extremely high proliferation rate (35).…”
Section: Discussionmentioning
confidence: 99%